Conceptual and methodological lessons for improving watershed management and research - Knox, Anna; Swallow, Brent M.; Johnson, Nancy L. (International Food Policy Research Institute, 2001)
Water sheds connect land units through flows of water, nutrients, and sediment—linking farmers, fishers, and urban dwellers in intricate relationships. How these flows affect people’s livelihoods depends on the biophysical attributes of the water shed as well as on the policies and institutions that shape human interactions within the watershed. Watersheds are managed at various social and spatial scales—from community management of small catchments to the transnational management of extensive river systems and lake basins.